If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 1)(x + -2 + 1) = 24 Reorder the terms: (1 + x)(x + -2 + 1) = 24 Reorder the terms: (1 + x)(-2 + 1 + x) = 24 Combine like terms: -2 + 1 = -1 (1 + x)(-1 + x) = 24 Multiply (1 + x) * (-1 + x) (1(-1 + x) + x(-1 + x)) = 24 ((-1 * 1 + x * 1) + x(-1 + x)) = 24 ((-1 + 1x) + x(-1 + x)) = 24 (-1 + 1x + (-1 * x + x * x)) = 24 (-1 + 1x + (-1x + x2)) = 24 Combine like terms: 1x + -1x = 0 (-1 + 0 + x2) = 24 (-1 + x2) = 24 Solving -1 + x2 = 24 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + x2 = 24 + 1 Combine like terms: -1 + 1 = 0 0 + x2 = 24 + 1 x2 = 24 + 1 Combine like terms: 24 + 1 = 25 x2 = 25 Simplifying x2 = 25 Take the square root of each side: x = {-5, 5}
| X^2+X-145=0 | | (x+3)(x+4)=x^2+7x+12 | | 2x=(-2)x | | X-10+x+2x+13=88 | | y=2.3x+5.4 | | -6(v+3)+3v+7=6v+7 | | 2a-(a+3)+3= | | 2(v+8)+5v=37 | | 9=5(u-3)+3u | | 28=4(w+6)-6w | | 1/9a=6 | | 6(-2-x)=-5(x+3) | | 5x-4-3x=14 | | -4=n | | 4e^3x+2=110 | | 10(s-4)=-132 | | 4e^3x+2=20 | | 10(s-4)=3 | | 10/3(10) | | 4e^3x-2=110 | | 2/3=7/x-4 | | -7-15x=23 | | 0.2+x=3 | | 2x+3y+6z=98 | | 60x=-32 | | 82=14+2x | | -5(7x+10)=-295 | | 3/4p=114 | | 26/x=13/8 | | y=x^2-17/2 | | 2c+5=3c | | 17x-4=4(4x+5)-16 |